Functional Correlates of Malnutrition Among Older Patients in a Primary Care Clinic in Northern, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Nutritional and functional impairments are assumed to be inevitable consequences of aging and they attract little attention in the primary care setting.Aim:To determine the association between malnutrition and functional status of the elderly to advocate for their routine screening in the primary care clinics and similar settings.Settings and Design:A cross-sectional descriptive study involving 352 patients of age ≥60 years who presented at the Family Medicine Clinic.Methods and Materials:The nutritional status was assessed using the Mini Nutritional Assessment tool, whereas functional capacity was assessed using Katz and Lawton index for the Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL), respectively.Statistical Analysis:Chi-square test and logistic regression analysis were used to determine associations between variables and nutritional status, and determinants of nutritional status, respectively.Results:The mean age of respondents was 67.9 ± 7.6 (60–95) years; 215 (61.1%) were women. The prevalence of malnutrition was 25.9% and of risk of malnutrition 53.1%. Advancing age (odds ratio [OR] = 4.93, 95% confidence interval [CI] =1.42–1.71,P≤ 0.001), low monthly income (OR = 9.29, 95% CI = 0.20–43.50,P= 0.005) and being functionally dependent (OR = 14.706, 95% CI = 1.26–3.35,P= 0.03 for ADL; OR = 17.51, 95% CI = 5.07–37.31,P= 0.004 for IADL) were the determinants of malnutrition in the elderly patients.Conclusion:The prevalence of malnutrition and those of at-risk of malnutrition was high. Advancing age, low income, and functional dependence were the independent correlates.